A new form of governance? Comparing the open method of coordination to multilateral surveillance by the IMF and the OECD - Armin Schäfer (Max Planck Institute for the Study of Societies, 2004)
The Open Method of Coordination (OMC) has received much attention in the recent EU-literature. The predominant view claims that the OMC is not only a new but also an effective policy-making instrument. This paper raises doubts about both claims by offering a comparison of soft law policy coordination in three international organizations. More specifically, this paper compares the European Employment Strategy - which was the first use of the OMC - to the Broad Economic Policy Guidelines of the EU, the OECD Economic Surveys, and the IMF Article IV Consultations. Based on expert interviews, it seeks to demonstrate that these procedures are forms of multilateral surveillance that do not differ in kind. Such a comparative analysis of the OMC refutes claims to its novelty. Having compared the four procedures, a more general model of multilateral surveillance consisting of six elements is generated that facilitates further comparisons. This paper concludes that governments select voluntarist procedures mainly to secure their own competencies rather than to realize common goals. Effective problem-solving is therefore not necessarily the dominant objective of soft law. – – Die EU-Literatur der letzten Jahre hat der Offenen Methode der Koordinierung (OMC) viel Aufmerksamkeit zukommen lassen. Die vorherrschende Sichtweise behauptet, dass die OMC nicht nur ein neues, sondern auch ein effektives Instrument der Politikgestaltung sei. Dieser Aufsatz stellt beide Aussagen infrage, indem es einen Vergleich verschiedener soft law-Verfahren von drei internationalen Organisationen vorlegt. Im Einzelnen vergleicht dieses Papier die Europäische Beschäftigungsstrategie - mit der die OMC zuerst entstanden ist - mit den Grundzügen der Wirtschaftspolitik der EU, den Länderberichten der OECD sowie den Artikel-IV-Konsultationen des Internationalen Währungsfonds. Auf der Grundlage von Experteninterviews wird gezeigt, dass alle vier Verfahren multilateraler Überwachung zugeordnet werden können und kein kategorischer Unterschied zwischen ihnen besteht. Eine solche vergleichende Analyse widerlegt die angenommene Neuheit der OMC. Aufbauend auf dem Vergleich der vier Verfahren wird dann ein allgemeines Modell multilateraler Überwachung entwickelt, welches aus sechs Elementen besteht und zukünftige Studien erleichtern wird. Dieser Aufsatz schließt mit der Beobachtung, dass Regierungen voluntaristische Verfahren eher deshalb wählen, um ihre eigenen Kompetenzen zu verteidigen als gemeinsame Ziele zu verwirklichen. Effektive Problemlösungsfähigkeit erscheint nicht als vorrangiges Anliegen von soft law.
Keywords: 300